Lacrimal sac mucoepidermoid carcinoma. Issue 9 (September 1986) - Blake, J; Mullaney, J; Gillan, J
Abstract : A single case of mucoepidermoid carcinoma of the lacrimal sac was considered worth reporting as there are only four other cases described in the literature. The importance of the correct histological diagnosis and the management are discussed. This appears to be the first study of the ultrastructure of lacrimal sac mucoepidermoid tumour.